2016
DOI: 10.1039/c5cp07440a
|View full text |Cite
|
Sign up to set email alerts
|

Al atom on MoO3(010) surface: adsorption and penetration using density functional theory

Abstract: Interfacial issues, such as the interfacial structure and the interdiffusion of atoms at the interface, are fundamental to the understanding of the ignition and reaction mechanisms of nanothermites. This study employs first-principle density functional theory to model Al/MoO3 by placing an Al adatom onto a unit cell of a MoO3(010) slab, and to probe the initiation of interfacial interactions of Al/MoO3 nanothermite by tracking the adsorption and subsurface-penetration of the Al adatom. The calculations show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…While step edges are common along the 〈001〉 direction of α-MoO 3 [19], these were not observed near the reaction zones. Based on the proposed sub-surface Al adsorption mechanism, Al atoms adsorb into the interstitial sites between adjacent terminal oxygen sites on the face of MoO 3 , minimally altering the bond length within the MoO 3 host [28]. Such a mechanism would produce an unperceivable change in surface topology, consistent with our observations.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While step edges are common along the 〈001〉 direction of α-MoO 3 [19], these were not observed near the reaction zones. Based on the proposed sub-surface Al adsorption mechanism, Al atoms adsorb into the interstitial sites between adjacent terminal oxygen sites on the face of MoO 3 , minimally altering the bond length within the MoO 3 host [28]. Such a mechanism would produce an unperceivable change in surface topology, consistent with our observations.…”
Section: Resultssupporting
confidence: 86%
“…Previous density functional theory (DFT) studies by others have investigated the interaction of atomic Al with the α-MoO 3 lattice. Wu et al examined the adsorption energy of individual Al adatoms at various sites along the (010) crystalline plane of α-MoO 3 [28]. This study showed that subsurface adsorption of an Al atom is more stable than surface adsorption, and that Al sub-surface adsorption occurs preferentially between terminal oxygen pairs in the 〈001〉 direction.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, on the exposed MoO 3 (010) surface, there are abundant four-fold hollow sites formed by four surface lattice oxygen atoms (Figure S1c). 22 These hollow sites are suitable for anchoring Ce 3+/4+ ions with an ionic radius of ∼1 Å. 23 Moreover, the loading of ceria is lower than the monolayer on the surface of MoO 3 calculated from its external specific surface area of ∼7 m 2 g −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lanthony et al investigated the initial oxidation of the Al(111) surface after CuO deposition and revealed the formation mechanisms of alumina and copper condensation in the bulk. Wu et al studied the adsorption of Al atoms on the MoO 3 (010) surface and found the initial mixture of Al, Mo, and O atoms. Gao et al disclosed the interactions between the Al adatom and the ZnO surface through a combination of experiments and theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%